Experimental study on repair of fractured rock mass by microbial induction technology. Issue 11 (20th November 2019) - Gao, Rugao; Luo, Yilin; Deng, Hongwei
Abstract : The surrounding rock mass is often required to have good strength and impermeability in underground engineering. Some grouting methods, such as the chemical grouting method and the cement grouting pressure pump method, are often applied to reform underground environment and improve the engineering performance of rock mass. However, the application of some traditional grouting materials would destroy the original environment in which the project is located. This paper focuses on the repairing effect of Bacillus pasteurii composites in fractured rocks. The repairing effect of microbial materials on fractured sandstone is analysed through nuclear magnetic resonance (NMR) and unconfined compression-shearing equipment. The result shows that the longer the repairing time is, the better the effect will be. After 42 days of repairing, the porosity of fractured sandstone decreases by 36.41%, the impermeability increases by 94.62%, and the compressive strength increases by 30.52%. Through the study of reaction mechanisms, this technology has the advantages of mild reaction conditions, no pollution and good environmental compatibility. The application of this technology to the maintenance of geotechnical engineering can provide new ideas for the research and development of new environmental grouting materials and underground space reconstruction technology.